Phenetic relationships among species of Berberis (Berberidaceae) from NW Patagonia - Bottini, M.C.J. (1997)
Phenetic relationships among species of Berberis (Berberidaceae) from NW Patagonia. Darwiniana 35: 115-129. Phenetic relationships among 11 species belonging to the genus Berberis from 46 populations of NW Patagonia Argentina, were studied using numerical techniques. The species are B. bidentata Lechl., B. buxifolia Lam., B. cabrerae Job, B. chillanensis Sprag. ex Sandwith, B. darwinii Hook., B. empetrifolia Lam., B. heterophylla Juss., B. linearifolia Phil., B. montana Gay, B. parodii Job and B. serrato-dentata Lechl. Fifty four morphological characters were defined (24 vegetative and 30 reproductive). Forty six populations (with a total of 288 individuals) were analyzed. Two main groups were distinguished from the phenogram. One consists of the populations of 10 spiny species; the other one is only formed by populations of B. serrato-dentata (without - or rarely / with scarce little weak - spines). Numerical analysis allowed to differentiate the species studied and each of the populations within a same species. This may be related to microambiental agents conditioning the phenotype. The results here obtained agree fairly well with the interespecific relationships previously published in the genus Berberis.